Curcumin-loaded PLGA microparticles integrated with ZnO/GelMA hydrogel microneedles for infectious wound healing and reduction of hypertrophic scars - Yifan Zhang; Ziyi Zhou; Na Liu; Jing Wang; Qingxia Guo; Yong You; Kaiping Mao; Yuanfei Wang; Weina Zhang; Tong Wu (Journal of Nanobiotechnology)
Abstract Excessive scarring can impede the normal skin movement, resulting in decreased body flexibility and functional abnormalities. These issues, in turn, impact patients’ daily lives and comfort. To prevent the pathological healing of infected wounds, this study developed a composite hydrogel microneedle that possesses stable mechanical properties and favorable biocompatibility. The microneedles, composed of gelatin methacryloyl hydrogels, were integrated with curcumin-loaded PLGA microparticles to promote wound healing and allow the controlled release of curcumin within a suitable timeframe, thereby minimizing the formation of hypertrophic scars. Zinc oxide nanoparticles were integrated into the base layer of the microneedle, forming a physical barrier and exhibiting significant antibacterial activity against both Staphylococcus aureus and Escherichia coli. Due to the unique structural and functional design, we demonstrated that this class of microneedles could accelerate the healing of infected wounds and downregulate the expression of α-SMA and collagen I in scar fibroblasts, thereby showing potential to inhibit scar formation. In vivo investigations further validated the effective repair of infected wounds in rat skin and demonstrated the inhibition of pathological scars using hypertrophic scar models in rabbit ears. Altogether, these materials exhibit promising potential to provide a new option for preventing pathological scarring in the treatment of infected wounds.